KARAKTERISTIK PENGGUNAAN BAHASA DALAM MAJALAH ISLAM - Nuryani Nuryani; Arif Budiman (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract: The purpose of this study is to describe the characteristics of language use in Islamic magazine. The characteristics are seen through the use of code switching and code mixing in the magazine. Islamic magazine was chosen because currently the development of religiosity in society tends to increase. This increase was also accompanied by an increase in reading options with Islamic content and nuances. The Islamic magazine chosen in this study is Hidayah Magazine. The theory used to dissect this research is the theory about the characteristics of the language presented by Jendra. The method used to retrieve data is the observation and note method. Based on the analysis that has been done, it can be concluded that in Hidayah magazines there are many events of code switching and code mixing. There is code switching in the form of clauses and sentences. In addition, code mixing is found in the form of words, compound words, and phrases. In terms of the type of code switching, it was found that metaphorical code switching was found. The events of code switching and code mixing in Hidayah magazines were found in various contexts, namely the ease of conveying information, feeling more “Islamic”, and adjusting to market segmentation.Abstrak: Tujuan penelitian ini adalah untuk mendeksripsikan karakteristik penggunaan bahasa dalam majalah Islam. Karakteristik dilihat melalui penggunaan alih kode dan campur kode dalam majalah tersebut. Majalah Islam dipilih karena saat ini perkembangan religiositas dalam masyarakat cenderung meningkat. Peningkatan tersebut juga dibarengi dengan peningkatan pilihan bacaan dengan muatan dan nuansa Islam. Majalah Islam yang dipilih dalam penelitian ini adalah Majalah Hidayah. Teori yang digunakan untuk membedah penelitian ini adalah teori mengenai karakteristik bahasa yang disampaikan oleh Jendra. Metode yang digunakan untuk mengambil data adalah metode simak dan catat. Berdasarkan analisis yang telah dilakukan dapat disimpulkan bahwa dalam majalah Hidayah banyak peristiwa alih kode dan campur kode. Terdapat alih kode dalam bentuk klausa dan kalimat. Selain itu, campur kode ditemukan dalam bentuk kata, kata majemuk, dan frasa. Dari sisi tipe alih kode ditemukan alih kode metaforis. Peristiwa alih kode dan campur kode dalam majalah Hidayah ditemukan dalam berbagai konteks, yakni kemudahan penyampaikan informasi, lebih merasakan “keislaman”, dan menyesuaikan dengan segmentasi pasar.